Case Report: Clinical and Genetic Characteristics of Pearson Syndrome in a Chinese Boy and 139 Patients - Ying, Yanqin; Liang, Yan; Luo, Xiaoping; Wei, Ming (Frontiers in Genetics, 2022)
Background: Pearson's syndrome (PS) is a rare multi-system disease caused by mitochondrial DNA deletion. Most PS cases are individual reports, and there is a lack of systematic analysis of clinical features and gene mutations in large samples. Objective: To report a case of PS and summarize the clinical features and genetic characteristics of PS by reviewing the literature. Methods: We reported a boy with severe anemia and multisystem disorder. Genetic etiology was identified by mitochondrial DNA sequencing. Clinical features and gene mutations were summarized and compared to other cases reported in the literature. Results: The patient had major clinical manifestations with recurrent anemia and multiple organ failure after infection. Mitochondrial DNA sequencing revealed a de novo heterozygous deletion of 3.063 kb (nt 6224-9287) with 75% heterogeneity in peripheral blood. A total of 139 PS cases were retrieved after a literature search. The most common initial symptom was refractory anemia requiring repeated blood transfusion (86.2%) and neutropenia or thrombocytopenia (20.8%), digestive system symptoms (26.9%) and failure to thrive (15.4%). During the course of disease, the involvement systems and symptoms were bone marrow failure (100%), metabolic disorders and digestive system (61.87%), failure to thrive (48.9%), renal involvement (42.45%), and pancreatic exocrine insufficiency (39.6%). The mean heterogeneity of mitochondrial DNA mutation in peripheral blood in deaths (76.29±11.86%, n=29) was higher than that in survivals (59.92±23.87%, n=26, P<0.01). Among the patients with the 4.977 kb deletion, the heterogeneity in peripheral blood in deaths (79.64±9.71%, n=11) was higher than that in survivals (56.67±27.65%, n=9, P<0.05). Conclusions: Pearson's syndrome can affect multi-system and mitochondrial DNA sequencing should be performed early. The heterogeneity in peripheral blood is related to prognosis.